Relationship of L1 Skills and L2 Aptitude to L2 Anxiety on the Foreign Language Classroom Anxiety Scale. Issue 4 (30th September 2013) - Sparks, Richard L.; Patton, Jon
Abstract : The Foreign Language Classroom Anxiety Scale (FLCAS) has been challenged on the grounds that it may also assess language learning skills. In this study, 128 students who had been administered measures of first language (L1) skills in elementary school were followed from 1st to 10th grade. Fifty‐three students had completed second language (L2) courses in high school where they were administered the Modern Language Aptitude Test (MLAT), FLCAS, and measures of L1 skills. A full information likelihood procedure (FIML) was used to conduct a path analysis and hierarchical regressions. The results showed that the FLCAS accounted for significant unique variance in L1 skills in elementary school several years before the students' engaged in L2 study as well as significant unique variance on the MLAT and L1 skills measured in high school. Hierarchical regressions found that the FLCAS predicted growth in L1 skills (reading, spelling, language) in elementary school and also from elementary to high school. Findings suggest that the FLCAS is likely to be measuring individual differences in students' language skills and/or self‐perceptions about their language learning skills rather than anxiety unique to L2 learning.